2010
DOI: 10.1189/jlb.0110028
|View full text |Cite
|
Sign up to set email alerts
|

The role of calcium signaling in phagocytosis

Abstract: Immune cells kill microbes by engulfing them in a membrane-enclosed compartment, the phagosome. Phagocytosis is initiated when foreign particles bind to receptors on the membrane of phagocytes. The best-studied phagocytic receptors, those for Igs (FcgammaR) and for complement proteins (CR), activate PLC and PLD, resulting in the intracellular production of the Ca(2+)-mobilizing second messengers InsP3 and S1P, respectively. The ensuing release of Ca(2+) from the ER activates SOCE channels in the plasma and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
189
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 206 publications
(198 citation statements)
references
References 201 publications
5
189
1
3
Order By: Relevance
“…The importance of Ca 2ϩ flux from endoplasmic reticulum stores during Fc␥R-induced phagocytosis was clearly shown using STIM1 KO macrophages (42), and our findings are consistent with these data. Some have suggested that Ca 2ϩ is not as important for phagocytosis of particles, but more important for the subsequent steps of phagosomal maturation (43). However, the data involving STIM1 KO macrophages and our data with SelK KO macrophages do not support this notion.…”
Section: Discussioncontrasting
confidence: 57%
“…The importance of Ca 2ϩ flux from endoplasmic reticulum stores during Fc␥R-induced phagocytosis was clearly shown using STIM1 KO macrophages (42), and our findings are consistent with these data. Some have suggested that Ca 2ϩ is not as important for phagocytosis of particles, but more important for the subsequent steps of phagosomal maturation (43). However, the data involving STIM1 KO macrophages and our data with SelK KO macrophages do not support this notion.…”
Section: Discussioncontrasting
confidence: 57%
“…Calcium ions are ubiquitous and versatile signalling molecules that play pleiotropic roles in the complex cellular organization and life cycle [38][39][40][41][42] , including during the egress from and the subsequent invasion of host cells by Apicomplexan parasites 25,[43][44][45] . The secretion route of eukaryotic cells has a gradient of Ca 2 þ concentration ([Ca 2 þ ]), being high in the ER (up to 400 mM), decreasing through the Golgi apparatus (250-130 mM) to reach values lower than 100 mM within secretory vesicles 38 .…”
Section: Post 3′ Utr Pbsub1mentioning
confidence: 99%
“…In the presence of PI3K inhibitors, incomplete phagosomes appear as actin-rich phagocytic cups, suggesting that PI3K may be involved in organizing the later stages of phagocytosis [13][14][15] . Ca 2 + signals are generated subsequent to the activation of FcγR through downstream processes that involve activation of PLCγ and are required for phagosome closure and maturation mainly through actin remodeling 16 . It is not clear whether Ca 2 + signalling has any role in the process of initiation.…”
mentioning
confidence: 99%